PENGARUH AUTHENTIC LEADERSHIP DAN EMPLOYEE ENGAGEMENT TERHADAP JOB SATISFACTION KARYAWAN PT CLARA CIPTA ABADI JAKARTA. - Wanda Hanifah (2021)
This study is a quantitative study to determine the effect of Authentic Leadership and Employee Engagement on Job Satisfaction. This research is motivated by the problems found regarding Authentic Leadership, Employee Engagement, and job satisfaction at PT Clara Cipta Abadi Jakarta. The data collection method used in this research is using a sampling technique, namely probability sampling with a sample of 95 employees of PT Clara Cipta Abadi Jakarta. In testing the hypothesis, this research uses the coefficient of determination test (R2), partial test (T test), and simultaneous test (F test). The results obtained from this study are (1) there is a significant influence between Authentic Leadership on Job Satisfaction of PT Clara Cipta Abadi Jakarta employees. (2) there is a significant influence between Employee Engagement on Job Satisfaction of PT Clara Cipta Abadi Jakarta employees. And (3) there is a significant influence between Authentic Leadership and Employee Engagement on Job Satisfaction of PT Clara Cipta Abadi Jakarta employees.